27‐3: Invited Paper: High‐Performance Sub‐50nm Channel Length 3D Monolithically Stackable Vertical IGZO TFTs for Active‐Matrix Application. Issue 1 (28th June 2022) - Duan, Xinlv; Huang, Kailiang; Feng, Junxiao; Yin, Shihui; Wang, Zhaogui; Jiao, Guangfan; Wu, Ying; Jing, Weiliang; Wang, Zhengbo; Li, Jingyu; Xu, Jeffrey; Chen, Chuanke; et al.
Abstract : For the first time, we propose a stackable vertical Channel‐All‐Around (CAA) IGZO FETs. The device is fabricated in a BEOL‐compatible process flow where the channel and gate stack is deposited by Plasma‐Enhanced Atomic Layer Deposition (PEALD). The impact of IGZO cycle ratio and plasma power on the device electrical performance are studied. An optimized 50nm‐channel‐length CAA IGZO FET achieved Ion >30μA/μm and Ioff below 1.8×10‐17μA/μm at VDS = 1V.